Fuzzy Inference System Sugeno Untuk Evaluasi Kinerja Pelayanan Pegawai Kantor Camat Batam Kota: Kinerja Karyawan, fuzzylogic, Metode Sugeno - Alfannisa Annurullah Fajrin (P3M Politeknik Negeri Banjarmasin, 2017)
In the process of institutional performance, the spearhead of employees becomes the first in the process of community service. Performance owned by each employee will show the quality of employees in performing their duties. It aims to see how far employees are performing, improving and monitoring performance for employees. So the chief employee can make the decision to choose the best of the best. Assessment is done on service orientation, integrity, discipline and cooperation. So far there is no system that can be used to find out how much performance owned by employees. Therefore, this research uses decision making system using fuzzy logic with Sugeno zero order method to assess the performance of employees in Tembesi , district Sagulung for data processing using MATLAB. The first step of completing employee performance evaluation using Sugeno method in determining input variables and well-defined output variables, the second step is to convert input variables into fuzzy circuit with fuzzification process the generates decision on output of employee service performance variable (Competent / Fair No Competent).